Hubungan Status Gizi Ibu Hamil dengan Kejadian Anemia pada Kehamilan di Puskesmas Maesaan - Kaligis, Yurike Hesty; Ilmiah, Widia Shofa (Pusat Riset dan Inovasi Nasional, 2025)
Anemia during pregnancy remains a prevalent health issue with adverse outcomes for both mother and fetus. This study aims to examine the relationship between maternal nutritional status and the incidence of anemia during pregnancy. A cross-sectional design was applied involving 40 pregnant women as respondents. Nutritional status was assessed through anthropometric measures, and hemoglobin levels were recorded from maternal health records. Data were analyzed using Spearman Rank correlation. The findings show that most respondents had fair to poor nutritional status, and all experienced anemia, with a predominance of moderate to severe levels. The correlation test revealed a very strong relationship between nutritional status and anemia (r = 0.916; p = 0.000). These results indicate that inadequate nutritional status strongly correlates with higher anemia severity. A monotonous diet, low in animal protein and vegetables, and limited nutrition knowledge contribute substantially to this condition. Furthermore, household decision-making around food often excludes the pregnant mother. Prevention strategies should emphasize nutrition education and behavioral change, rather than relying solely on supplementation. Health services should also involve families in sustaining healthy dietary practices during pregnancy.